2008
DOI: 10.1258/jtt.2008.003015
|View full text |Cite
|
Sign up to set email alerts
|

A pilot study of mobile phone-based therapy for obese patients

Abstract: We conducted a pilot study to assess the feasibility of a web-based therapy management system with mobile phone access to support obese patients. A total of 25 patients participated in the study. The mean age of the patients was 48 years. The mean body mass index of the patients at recruitment was 35.6 kg/m(2). The mean observation period was 70 days. A total of 361 successful data transmissions was performed -- the mean number of transmissions per patient was 14. The total number of outgoing reminder messages… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
29
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 6 publications
1
29
0
Order By: Relevance
“…Thirteen studies were identified, and of these, 4 met our inclusion criteria (Table 3). Studies were excluded because they did not report weight loss outcomes (nϭ3), [82][83][84] did not use a randomized controlled design (nϭ4), [85][86][87][88] or the phones used were standard landline phones (nϭ2). 49,89 All 4 studies enrolled primarily white women and were conducted in the community.…”
Section: Handheld and Other Devices For Use In Behavioral Weight Lossmentioning
confidence: 99%
“…Thirteen studies were identified, and of these, 4 met our inclusion criteria (Table 3). Studies were excluded because they did not report weight loss outcomes (nϭ3), [82][83][84] did not use a randomized controlled design (nϭ4), [85][86][87][88] or the phones used were standard landline phones (nϭ2). 49,89 All 4 studies enrolled primarily white women and were conducted in the community.…”
Section: Handheld and Other Devices For Use In Behavioral Weight Lossmentioning
confidence: 99%
“…PICARD was designed so as to be able to receive data from remote monitoring systems and was already used in several studies concerning heart failure (Scherr et al, 2009), psoriasis (Hayn et al, 2009), diabetes (Kollmann et al, 2007c), and adipositas (Morak et al, 2008). Currently it is also used in a routine remote monitoring scenario (Kastner et al, 2010).…”
Section: Upload Of Data From Remote Monitoring Systemsmentioning
confidence: 99%
“…Chronic diseases such as hypertension, type 2 diabetes, cardiovascular disease and stroke are often a result of carrying this excessive weight [3][4][5][6]. The ramifications of being overweight and obesity extend beyond the aforementioned health consequences.…”
Section: Introductionmentioning
confidence: 99%